2014
DOI: 10.1111/jog.12512
|View full text |Cite
|
Sign up to set email alerts
|

Obstetricians and gynecologists: Which characteristics do Israeli lesbians prefer?

Abstract: Overwhelmingly lesbians prefer sexually tolerant obstetricians/gynecologists regardless of their gender; however, only a small number of lesbian subjects in this study considered their obstetricians/gynecologists as displaying this characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…In comparison with other possible factors, gender preference is likely to have a stronger impact when choosing health professionals engaged in intimate and psychosocial medical treatment. Indeed, several previously published studies found that women tend to prefer female physicians, especially when it comes to obstetrical/gynecological issues [1, 2, 12, 13]. Data regarding other intimate specialties such as breast surgery are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other possible factors, gender preference is likely to have a stronger impact when choosing health professionals engaged in intimate and psychosocial medical treatment. Indeed, several previously published studies found that women tend to prefer female physicians, especially when it comes to obstetrical/gynecological issues [1, 2, 12, 13]. Data regarding other intimate specialties such as breast surgery are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…A long history of discrimination and oppression means that many LGBTQ people are reluctant to be open about their sexuality or gender identity, despite positive changes in societal attitudes. Numerous studies demonstrate that many LGBTQ patients show a marked preference for LGBTQ or LGBTQ‐friendly health care providers. It therefore follows that LGBTQ health professionals have distinct information needs, either because of their patients’ or because of their own health information needs, an observation confirmed by Fikar & Keith's respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies 39,40 demonstrate that many LGBTQ patients show a marked preference for LGBTQ or LGBTQ-friendly health care providers. It therefore follows that LGBTQ health professionals have distinct information needs, either because of their patients' or because of their own health information needs, an observation confirmed by Fikar & Keith's respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Sampietro-Colom et al noted that although there are many publications regarding same sex preference, it is limited to a fairly homogeneous population (Caucasian women from the United States, the United Kingdom, and Canada) [ 5 ]. Several recent publications have discussed the preferences of Arab women [ 6 - 8 ], Asian women [ 9 ], and Israeli women [ 10 - 13 ], and many explanations were given for their preferring same-sex physicians, among them the nature of the required clinical care, the physician’s attitude and communication style, and the patient’s stereotyping of physicians [ 14 , 15 ]. Notably, the most frequent reasons for the patient’s choices were religious beliefs and cultural traditions [ 6 - 8 ], with sex being the most important parameter among the very religious communities [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%